Fresh submarine groundwater discharge offshore Wellington (New Zealand): hydroacoustic characteristics and its influence on seafloor geomorphology - Hoffmann, Jasper J. L.; Mountjoy, Joshu J.; Spain, Erica; Gall, Mark; Tait, Leigh W.; Ladroit, Yoann; Micallef, Aaron (Frontiers in Marine Science, 2023)
Fresh submarine groundwater discharge (FSGD) influences the biogeochemistry of coastal areas and can be a proxy for potential untapped resources of offshore freshened groundwater (OFG). In most areas however, the onshore-offshore connection and the recharge characteristics of offshore aquifers are poorly constrained, making a potential exploitation of this resource challenging. Offshore Wellington (New Zealand), a well-defined onshore aquifer system extends beneath the harbour, where substantial amounts of freshwater seep out from the ocean floor. The aquifer system has been studied in detail and recently the first attempts worldwide have been made here to use the offshore groundwater as a future source of drinking water. However, the locations and extent of FSGD as well as its influence on seafloor morphology are still poorly understood. Exact localisation of FSGD sites is essential to sample and quantify discharging waters but remains challenging due to a lack of robust and appropriate measurement procedures. Novel sensing strategies, such as the influence of seeping groundwater on hydroacoustic water column reflectivity could greatly improve the identification of groundwater discharge locations worldwide. Therefore, we use a multidisciplinary dataset and evaluate different methodologies to map the spatial extent of FSGD sites and determine their geomorphologic expressions on the seafloor of Wellington Harbour. In this study, single and multibeam hydroacoustics and towfish (temperature, salinity and turbidity) transects were combined with remotely operated vehicles (ROV) dives and sediment cores to better characterise FSGD sites. We observed several hundred seafloor depressions (pockmarks) that we attribute to continuous seepage of gas and groundwater from the seafloor. Different pockmark morphologies indicate different fluid flow regimes and the persistent flow allows even small pockmarks to remain unchanged over time, while the geomorphologic expressions of anchor scours on the seafloor diminish in the same region. Enhanced hydroacoustic reflections in the water column within and